Environmental & architectural phenomenology. Vol. 8, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1997)
Vol. 8, No. 2, Spring 1997 (includes “items of interest,” "citations received,” book review of Michael Southworth's Streets and the Shaping of Towns and Cities, magazine review of This England, and essays by Kay Toombs & Gwendolyn Scott).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals